Geriatric otorhinolaryngology: reasons for outpatient referrals from generalists to ENT specialists - Alves, Clara Serdoura (2022)
Purpose: To determine the main symptoms leading to referral of geriatric patients from primary care to otorhinolaryngology. Methods: Retrospective, observational study performed on patients aged 65 and older, referred from Primary Care to the Otorhinolaryngology and Head and Neck Surgery department of a tertiary centre during 2019 and 2020. Symptoms leading to otorhinolaryngological referral were categorized as "Oto-neurological symptoms", "Nasal symptoms", "Pharyngolaryngeal symptoms", "Other Head and Neck symptoms" and "Other Reasons". Data regarding age, gender and whether patients maintain follow-up or have been discharged was also collected. Results: The study population included a total of 1304 patients (697 female; 607 male). Oto-neurological symptoms were found to be the most prevalent symptoms, with 65% of patients reporting oto-neurological symptoms as at least one of the reasons for referral. Hearing loss was the most commonly reported symptom, with an association found between this symptom and age (p < 0.001). Results also showed an association between the female gender and vertigo/dizziness (p < 0.001) and tinnitus (p = 0.007). An association between the male gender and nasal symptoms was also found (p = 0.018), particularly nasal obstruction (p = 0.003) and epistaxis (p = 0.028). No statistically significant associations were found among the pharyngolaryngeal group. Conclusions: This retrospective observational study allowed for a better understanding of the type of otorhinolaryngological symptoms affecting elderly patients and driving otorhinolaryngology evaluation, cementing hearing loss as one of the major complaints among older adults and allowing for a better preparation by otorhinolaryngologists for the changing needs of this subset of the population.